Innovation and its role within Social Enterprises: A case study of Hill Holt Wood - Christian, Mark (2012)
This paper considers the role of innovation within organisations and specifically within the context of social enterprises. After defining and charting the rise of the social enterprise movement, different views on innovation, where it can derive from and the different forms it can take will be considered. A case study is presented in the form of Hill Holt Wood, an environmental social enterprise, based in Lincolnshire, and the role innovation has played in ensuring that the enterprise has grown, been successful in its social mission and has remained a sustainable operation. Best practices are taken from this example which may help inform existing enterprises and those interested in setting up new social enterprises in the future.